Nursing students' knowledge and attitude in relation to COVID-19 prevention behavior - Vhania Dhominica Bani; Pinka Kinanthi Gusti; Marlita Enjel Rawul; Martina Pakpahan; Ester Silitonga (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to determine the correlation between nursing students' level of knowledge and attitudes toward COVID-19 prevention behavior. Methods: a cross-sectional study was carried out at the Private University in Indonesia. Accidental sampling was used to select 188 third-year bachelor's nursing students as respondents. Data collection was conducted through an online questionnaire (Cronbach's Alpha 0.799-0.959) consisting of 27 questions. The data were analyzed descriptively and inferentially. Results: as many as 49.5 % of respondents had high knowledge, 98.4 % had a positive attitude, and 89.9 % had positive behavior in preventing COVID-19 transmission. The Chi-square test revealed that knowledge has no correlation with COVID-19 prevention behavior (p-value 0.864), but attitude did (p-value 0.027). Conclusions: nursing students' attitudes are related to behavior in preventing COVID-19. Nursing students are expected to maintain positive attitudes and behaviors toward COVID-19 prevention as future health workers at the forefront of health services.